Mathematical cognition - Royer, James M., 1941- (Current perspectives on cognition, learning, and instruction., 2003)
This book is divided into seven chapters including: a broad overview of mathematical cognition; development of mathematical cognition; working memory, automaticity and mathematical problem solving; mathematical problem solving; and methematical learning disabilities.